2003
DOI: 10.1212/wnl.61.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Acute motor conduction block neuropathy Another Guillain–Barré syndrome variant

Abstract: Acute motor neuropathy with normal or brisk tendon reflexes, conduction block, and fast recovery appears to be a variant of Guillain-Barré syndrome. Conduction block may result from immune-mediated conduction failure at the nodes of Ranvier without demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
1
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 38 publications
5
96
1
11
Order By: Relevance
“…[18][19][20][21] In the current study, we found significant associations of reversible conduction failure with IgG anti-GM1, -GalNAc-GD1a, -GD1b, and -LM1/GA1 antibodies. Reversible conduction failure was first described in 1998 and this was followed by reports of similar findings in other cohorts.…”
Section: Resultssupporting
confidence: 59%
“…[18][19][20][21] In the current study, we found significant associations of reversible conduction failure with IgG anti-GM1, -GalNAc-GD1a, -GD1b, and -LM1/GA1 antibodies. Reversible conduction failure was first described in 1998 and this was followed by reports of similar findings in other cohorts.…”
Section: Resultssupporting
confidence: 59%
“…Although hyporeflexia or areflexia is the hallmark of GBS, normal reflexes or hyperreflexia is not a finding inconsistent with the diagnosis of GBS. The variants most commonly reported to be associated with retained or brisk reflexes are AMAN, acute motor conduction block neuropathy, and acute facial diplegia with brisk reflexes 8,9 . The incidence of hyperreflexia in AMAN is reported to be between 33% and 48% 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…Preserved reflexes and even hyperreflexia may occur in patients with pure motor GBS and are not inconsistent with the diagnosis. It is more appropriate to classify this neuropathy as a GBS variant, which Capasso et al, suggest calling "acute motor conduction block neuropathy," emphasizing the presence of conduction blocks and avoiding the pathophysiologic implication that all conduction blocks are demyelinating in nature 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute motor conduction block neuropathy presents with symmetric proximal and distal weakness without sensory abnormalities with normal or even brisk reflexes following C. Jejuni enteritis. Elevated IgG antibody titers to GD1a and GM1 have been reported and electrophysiology showed normal sensory conductions and partial motor conduction block in intermediate and distal nerve segments that resolves within 2 to 5 weeks [28].…”
Section: Gbs Variantsmentioning
confidence: 99%